A liberdade e os fundamentos da prisão cautelar - Branco Junior, Luiz Carlos (2010)
To point the main points of the present dissertation, aiming at to reach the degree of master in Legal Philosophy, leaving of the onslaught in clarifying the close relations between the freedom locomotion human being and the restrictions imposed for the government with the action for a provisional arrest, the studies flow off the finding of the restriction of the freedom in specific cases pointed by the law, while other possibilities to be adopted as forms of action for a provisional arrest, as occurred with the adoption of the temporary arrest in 1989, by the Law nº 7960, of December 21st. The dynamics of the freedom must be displayed with the connection between its development, its evolution and its origination, all these points based on the historical and philosophical progress of the institute. Likely for its importance, the freedom served as an introduction for the subjects related to the action for a provisional arrest, initiating the studies of beddings of this and, then, immediately afterwards, the basic slight knowledge on the institute of the action for a provisional arrest also had been studied in its main aspects. All this to reach the principles authorizer of the species of restrictions of the freedom promoted by the government, without sublime the nature of the freedom in a scene of principles and rules that can establish collisions in several formats, which are the collisions between principles and norms, or only between norms or solely between principles. Although the occurrence in the Brazilian social environment is raised, as already approximate close to the half of the arrests occurred during one year, the action for a provisional arrest the same does not occupy space in the entourage doctrinaire, reaching an emptiness without precedents in the Legal philosophy. The reality of the action for a provisional arrest is presented as chaotic, postulating imperative changes, here the determinism contribute in two aspects, firstly to understand the reality, secondly to transform the lamentable situation into plausible conditions for the life in society. The disordered current state if does not present as idoneous for future modifications, however, it certifies positively that the hypotheses of action for a provisional arrest are knowledge of all. For the future balance of the action for a provisional arrest, the elementary confusions must be unmake and the arrangement of the present must concern the mistakes and successes of the past and, solely thus, the future of stability will be acquired with precision